Sustainability in the hospitality industry principles of sustainable operations - Legrand, Willy; Sloan, Philip; Chen, Joseph S. (Londo Routledge, 2017)
"Sustainability in the Hospitality Industry, Third Edition, is the only book available to introduce students to economic, environmental and socially sustainable issues specifically facing the industry as well as exploring ideas, solutions and strategies of how to manage operations in a sustainable way."--Provided by publisher.
1. The rationale for sustainable development -- 2. Sustainable development and the hospitality industry -- 3. Energy management -- 4. Waste management -- 5. Water management -- 6. Eco-design and facilities development -- 7. Food security -- 8. Agriculture and sourcing -- 9. Sustainable food and beverage management -- 10. Responsible consumer behaviour -- 11. Accessibility in hospitality and tourism -- 12. Corporate social responsibility and social entrepreneurship -- 13. Responsible marketing and branding -- 14. Environmental management systems, sustainability performance and auditing -- 15. Certification processes and ecolabels -- 16. Investing, financing, performing and decision-making in sustainability -- 17. Internalising externalities and environmental accountability -- 18. Benchmarking, reporting and communicating sustainability.
Earlier editions were entered under Sloan, Philip.
Includes bibliographical references and index.
Keywords: Hospitality industry -- Management; Hospitality industry -- Environmental aspects; Social responsibility of business; Sustainability